The EU as an Observer of Elections in Africa: Aims, Methods and Consequences (2000s) - Kulkova, Olga S. (Africana Studia, 2020)
The article analyses the efforts of the European Union in the 2000s to promote the democracy in Africa by ensuring that elections in the countries of the continent were transparent, free and fair. Therefore, the EU sends its election observation missions to monitor African elections and supports a range of various supplementary initiatives. The article looks at the aims and methods used by the EU observer missions, on the examples of various country cases (Kenya, Liberia, Zimbabwe, Angola, Nigeria), and discusses the consequences which such missions might have both for the EU, the government and society of a given African country.